Pengaruh Restrukturisasi KUR, Efektivitas Penggunaan Dana KUR Dan Intellectual Capital Terhadap Kinerja Keuangan UMKM Pengguna KUR Di Kabupaten Buleleng Ditengah Pandemi Covid-19 - I Gusti Ayu Sri Prayatninggrum; I Gede Putu Banu Astawa (Universitas Pendidikan Ganesha, 2022)
The purpose of this research is to find out the partial and simultaneous effect of KUR restructuring, the effectiveness of using KUR funds, human capital, customer capital and structural capital on the financial performance of MSMEs using KUR in Buleleng Regency in the midst of the covid-19 pandemic. Quantitative methods are used as research methods in this research with questionnaires as primary data. MSMEs using KUR in Buleleng Regency amounted to 21,577 MSMEs were used as the population in this research and recorded at the Disdagperinkopukm Buleleng Regency. Isaac and Michael's technique was used to determine the sample in this research and obtained a sample of 352 MSMEs. Research data was collected using a questionnaire distributed via online in the form of a google form and processing it with multiple linear regression analysis test using SPSS statistic version 25. This research resulted in KUR restructuring, the effectiveness of using KUR funds, human capital, customer capital and structural positive and significant influence partially and simultaneous on the financial performance of MSMEs using KUR in Buleleng Regency in the midst of the covid-19 pandemic. Keywords: Financial performance of UMKM, KUR restructuring, Effectiveness of the use of KUR funds, and Intellectual capital.